PENGEMBANGAN KURIKULUM 2013 MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 1 MIMBAAN - Reky Lidyawati (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
In accordance of the preliminary study has been conducted by researchers, has obtained information that in an elementary school in the documentation has been set up matters relating to the development needs of the curriculum in 2013, but at the level of implementation there are several things that need to be addressed, because it is still many teachers find it difficult to implement the curriculum in 2013. There are still many students who do not succeed in the learning process is a problem that must be addressed immediately, so found appropriate learning strategies need to be developed in the learning process, so that the learning process can be flawlessly and produce a quality output. Principals and teachers is the key person in the successful implementation of learning in school. They are the ones who are given the responsibility to develop and implement curriculum. From this phenomenon, the principals and teachers have a major role in the dynamics of education in schools, including also had to take the role of the school committee. This study is a qualitative research, a study that produces descriptive data in the form of data written or spoken of people and behaviors that can be observed